Reformed and feminist : a challenge to the church - Van Wijk-Bos, Johanna W.H., 1940-- (Louisville, Kentucky Westminster/Knox Press, 1991)
This fresh, insightful book explores the nature and function of biblical authority for Christian feminism. Johanna van Wijk-Bos demonstrates, from a Reformed/Calvinist context, the importance of sola scriptura for feminist biblical studies. She illustrates the ways in which biblical authority undergirds and expands feminist perspectives.
Reformed and feminist
Includes bibliographical references
Keywords: Feminism -- Biblical teaching; Feminism -- Religious aspects -- Presbyterian Church; Women in the Bible; Bible -- Evidences, authority, etc. -- History of doctrines -- 20th century; Women in the Presbyterian Church; Presbyterian Church -- Doctrines; Reformed Church -- Doctrines; Van Wijk-Bos, Johanna W.H., 1940-